The effect of cold exposure on serum cholesterol is dependent upon ApoE. (July 2021) - He, Fang; Su, Wenquan; Wu, Rongrong; Li, He; Lou, Lixia; Wu, Aiming; Xie, Lifang; Du, Yawei; Wu, Shengxian
Abstract: Background: Several lines of evidence indicate that cold stimulation may not only activate brown adipose tissue (BAT) and the white adipose tissue (WAT), but also regulate the lipid metabolism and influence the development of atherosclerosis. However, the study of cold exposure affecting cholesterol metabolism have opposite results in different experiments, and Apolipoprotein E (ApoE) may play an important role. There is still a lack of complete research to illustrate this problem. Methods: In this study, we first analyzed and discussed the activation of interscapular brown adipose tissue (iBAT), inguinal white adipose tissue (iWAT) and epididymal white adipose tissue (eWAT) under cold exposure (4 °C) in male wild-type C57BL/6 J (WT) and ApoE-deficient mice (ApoE −/− ) fed high-fat diet (HFD) for 4 weeks. Subsequently, we investigated the effect of cold exposure on blood lipid profiles in both models. We further explored whether cold exposure can reduce serum cholesterol. Results: In both WT and ApoE −/− mice, cold exposure activates iBAT and iWAT, as well as hardly affects eWAT. In WT mice, 4 weeks cold exposure (4 °C) reduces serum triglyceride by 28%, cholesterol by 30% and LDL-cholesterol by 63%. In ApoE −/− mice, cold stimulation decreases serum triglyceride by 59%, but increases cholesterol by 20% and LDL-cholesterol by 25%. Conclusions: Based on these findings, we conclude that cold exposure decreases serum cholesterol is dependent upon the existence of ApoE. Highlights: We showed that cold exposure activated adipose tissues and reduced serum triglyceride in both C57BL/6 J and ApoE−/− mice. Cold exposure decreased serum cholesterol crucially depends on ApoE. We uncovered an important role of cold exposure in regulating adipose tissue thermogenesis and cholesterol metabolism, and we established the foundation for future studies that epidemiological studies on cold-related CVD should distinguish if patients have a functional ApoE–LDLR axis.